1994
DOI: 10.1111/j.1365-2125.1994.tb04266.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose of midazolam should be reduced during diltiazem and verapamil treatments.

Abstract: 1. The effects of diltiazem and verapamil on the pharmacokinetics and pharmacodynamics of midazolam were investigated in a double‐blind randomized cross‐over study of three phases. 2. Nine healthy volunteers were given orally diltiazem (60 mg), verapamil (80 mg) or placebo three times daily for 2 days. On the second day they received a 15 mg oral dose of midazolam, after which plasma samples were collected and performance tests carried out for 17 h. 3. The area under the midazolam concentration‐time curve was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(70 citation statements)
references
References 15 publications
1
69
0
Order By: Relevance
“…Thummel et al [7] demonstrated an excellent correlation (r = 0.93, p < 0.001) between in vivo total midazolam clearance and hepatic CYP3A content measured ex vivo in liver transplant patients. Midazolam has met most of the putative criteria as a selective and sensitive probe for CYP3A activity [1,[6][7][8], has demonstrated a small degree of intraindividual variability over 3 months, and is not affected by gender or menstrual cycle phase [9]. Midazolam has the advantages of intravenous administration to avoid pre-systemic metabolism, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Thummel et al [7] demonstrated an excellent correlation (r = 0.93, p < 0.001) between in vivo total midazolam clearance and hepatic CYP3A content measured ex vivo in liver transplant patients. Midazolam has met most of the putative criteria as a selective and sensitive probe for CYP3A activity [1,[6][7][8], has demonstrated a small degree of intraindividual variability over 3 months, and is not affected by gender or menstrual cycle phase [9]. Midazolam has the advantages of intravenous administration to avoid pre-systemic metabolism, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…McDonnell et al (68) demonstrated that co-administration of atorvastatin in patients receiving intravenous midazolam undergoing general anesthesia resulted in an increase in the area-under-the-curve (AUC) and a decrease in the clearance of midazolam. Although atorvastatin in particular was examined in this trial, most CYP3A4-metabolized statins In addition, studies of diltiazem and verapamil have also demonstrated increases in the peak concentration, AUC, and a decrease in the clearance of intravenous midazolam (69). A combination of non-dihydropyridine (DHP) CCBs and midazolam has also been shown to result in more profound and prolonged sedation than non-exposure to the interaction (70).…”
Section: Antiplateletsmentioning
confidence: 96%
“…Knowledge of adverse drug interactions is imperative in the practice of anesthesia. In 1994, it was reported that oral administration of CCB diltiazem or verapamil with midazolam prolonged the sedative and hypnotic effects of midazolam in nine healthy volunteers (Backman et al, 1994). Investigation into the effect of CCB on the metabolism of midazolam was warranted because these drugs are frequently administered in the practice of anesthesia.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Prolonged and profound sedative effects were also observed. The study concluded that if the administration of midazolam could not be avoided than the dose of midazolam should be reduced if given with diltiazem or verapamil (Backman et al, 1994). In another study published in 1996, 30 patients having coronary artery bypass grafting, were randomly assigned to receive either diltiazem two hours before induction of anesthesia with midazolam or a placebo in a double-blind study.…”
Section: Calcium Channel Blockers and Midazolammentioning
confidence: 99%
See 1 more Smart Citation